GRAMMATICAL SIMILARITIES OF ENGLISH AND UZBEK LANGUAGE - Ramazonov, Shohruh Nusratillo o‘g‘li (Educational Research in Universal Sciences, 2023)
This article discusses the classification of word groups in modern English and Uzbek, primary grammatical categories, the division of existing words in each specific language into specific groups, lexical and lexical-grammatical, morphological forms according to their meanings to the generality of words belonging to a particular group.